CONSUMER PERCEPTION, BUYING BEHAVIOUR AND LEVEL OF SATISFACTION TOWARDS ORGANIC FOOD PRODUCTS WITH SPECIAL REFERENCE TO ANNUR TALUK - Dr. M. Prakash; Ms. Madhumithra D, (EPRA International Journal of Environmental Economics, Commerce and Educational Management (ECEM), 2023)
The aim of this project is to investigate the perception trend of organic food. The project will begin with a review of the existing literature on organic food products, including their definitions, benefits, advantages, disadvantages, categories, role of government in organic food products, and Indian organic logos. This will be followed by a buying behavior to identify the trends and growth patterns of organic food products in annur taluk. The project will also examine level of satisfaction towards organic food products. The findings of the project will provide insights into the organic food product market, consumer behavior, and the potential for future growth in this sector. Ultimately, the project will contribute to a better understanding of the organic food product industry and help stakeholders make informed decisions.